PEDAGOGICAL CONDITIONS OF FORMATION OF REFLEXIVE SKILLS OF STUDENT UNIVERSITY STUDENTS (Pedagogy of Higher and Secondary Education, 2008)
Didactic terms, coopérant forming of abilities of reflections of students of pedagogical universities, are examined in the article.